Job Satisfaction and Employee Engagement among Human Resources Staff of Thai Private Higher Education Institutions - Tepayakul, Ruechuta; Rinthaisong, Idsaratt (The Journal of Behavioral Science, 2018)
It is clear from previous research that job satisfaction and employee engagement are critical to organizational success. However, the literature on the relationship of job satisfaction to employee engagement in human resources staff (HR staff) very limited. Therefore, the objective of this study was to establish the relationship of job satisfaction and employee engagement and to identify a model of job satisfaction and employee engagement among HR staff in private higher education institutions (PHEIs) in Thailand. A questionnaire was developed from a literature review and was administered to a sample of 220 HR staff. The responses were analyzed through confirmatory factor analysis. This study revealed that there is positive relationship between job satisfaction and employee engagement with a statistically significant direct effect. The findings of this research will be helpful in encouraging further activities to improve the job satisfaction and employee engagement of HR staff in PHEIs. It is recommended that the research methodology and the model developed should be extended to different sectors in future research.